KOMUNIKASI ADVOKASI KLARIFIKASI FAKTA PEMBERITAAN HOAKS PADA INSTAGRAM @JALAHOAKS - Danang Wiryawan Nugroho; Rini Riyantini; Lusia Handayani (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Problems regarding the widespread spread of hoax news often occur through social media. The massive circulation of hoaxes that occurs is due to the low level of digital literacy in the community in filtering information that can potentially disturb the public and disrupt public order. Government public bodies are considered to have the responsibility to eradicate social problems related to the circulation of hoax news that occurs in the community. This prompted the DKI Jakarta Provincial Government of Communication, Information and Statistics to create the Jakarta Lawan Hoaks (Jalahoaks) channel to carry out advocacy activities. This study aims to analyze the advocacy communication process for truth clarification on hoax news on Instagram @Jalahoaks. This research uses a qualitative approach with exploratory research and case study methods. The theory used in this research is advocacy communication. The results of this study indicate that the advocacy communication process carried out on Instagram @Jalahoaks can be successful and run effectively, based on analysis, strategy, mobilization, action, evaluation, and sustainability. The use and maximization of Instagram social media as a means to clarify the facts of hoax news can support and facilitate the advocacy communication process carried out by Jalahoaks.